Endoscopic cartilage butterfly myringoplasty in children - Akyigit, Abdulvahap; Karlidag, Turgut; Keles, Erol; Kaygusuz, Irfan; Yalcin, Sinasi; Polat, Cahit; Eroglu, Orkun (Elsevier Sci Ltd, 2017)
Objective: The present study evaluated the results of the graft success rate and hearing gain of children who underwent endoscopic inlay butterfly myringoplasty due to chronic otitis media. Methods: The study included 32 pediatric patients aged between 8 and 17, who had endoscopic inlay butterfly myringoplasty with the diagnosis of chronic otitis media between September 2012 and January 2015 in Elazig Training and Research Hospital Otorhinolaryngology Clinic and Firat University Otorhinolaryngology Clinic. All patients' demographics, perforation size, and hearing status were examined. Results: Tympanic membrane perforation Was <= 3 mm in 12 patients and between 3 and 6 mm in 20 patients. The air-bone gap (ABG) of the patients was 18.5 +/- 6.29 dB preoperatively, 8.81 +/- 3.53 dB postoperatively second month, 8.09 +/- 3.55 dB postoperatively sixth month, and 7.96 +/- 3.32 dB postoperatively 12th month. Two (6.3%) of the patients had postoperative myringitis. Two (6.3%) patients had recurrent perforation in the postoperative follow-ups. Conclusion: In children, endoscopic inlay butterfly tympanoplasty is a surgical technique with short duration, high graft success, effective hearing reconstruction, and high levels of postoperative patient comfort. (C) 2016 Elsevier Ireland Ltd. All rights reserved.
Keywords: Butterfly myringoplasty; Endoscopic; Pediatric